Environmental management : communication and conflict during environmental inspection : a case study of Uppsala Municipality (Sweden) - Yang, Edmond (SLU/Dept. of Urban and Rural Development, 2010)

(untitled)
To avert environmental degradation, the governments of most nations have put in place environmental regulations to ensure sustainable development. But environmental laws can not solve the problem alone; communication is an important tool in ensuring environmental regulation and avoiding conflict during the process of environmental inspection. The aim of this paper was to study the role of communication in environmental inspection. Interviews were used as the principle method for data collection.